HUBUNGAN POLA MAKAN DENGAN KEJADIAN GASTRITIS PADA MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS ISLAM ASSYAFI’IYAH JAKARTA - Siti Fatimah; Fitri NA (Afiat, 2016)
Introdution Gastritis or commonly known as ulcer disease is a very disturbing disease but oftenoverlooked. Gastritis occurs because of bad diet, thereby causing inflammation on the stomach lining.If it is allowed to continue, it would damage the stomach and the risk of gastric cancer causing death.The research objective is to determine the relationship between diet and gastritis incident on thestudents of Faculty of Health Sciences at As-Syafi’iyah Islamic University Jakarta. Correlativedescriptive research method with cross sectional approach was used with a population of 277 people.The samples were taken by Simple Random Sampling technique as many as 164 respondents. Theanalyses used were univariate and bivariate using chi-square by = 5%. The results show that thereis a significant relationship between the gastritis incident and diet statistically because of the value ofchi-square (2) = 8.079 higher than the value of chi-square table and (2) 0.05 (1) = 3.84. The conclusionis that there is a significant relationship between diet and gastritis incident on the students of theFaculty of Health Sciences at As-Syafi’iyah Islamic University Jakarta with the closeness of 0.3069.The recommendation is that it is expected to increase the knowledge of students of faculty of healthsciences and it can be added the library reference and insight to As-Syafi’iyah Islamic UniversityJakarta.